Giorgio Agamben, J. G. Farrell's The Singapore Grip, and the Colonial Dispositif. (21st October 2016) - Li, Victor
Abstract : In his Afterword to The Singapore Grip, J. G. Farrell thanks Giorgio and Ginevra Agamben for suggesting the phrase that became the title of his novel. What can we make of this surprising and unexpected connection between an Anglo-Irish author's novel about colonial Singapore on the eve of its fall to the Japanese army during World War II and Agamben's writings on biopolitics? Despite the serendipitous nature of the encounter between the two writers and the lack of any causal relation between their works, my paper argues that there is an unacknowledged affinity that allows us to open them up to what Agamben calls their Entwicklungsfähigkeit, "the locus and the moment wherein they are susceptible to development, " thereby bringing out the biopolitical elements in Farrell's novel and turning Agamben's insights into dispositifs or biopolitical apparatuses in the direction of the analysis of colonial rule.